Fulvestrant treatment alters MDM2 protein turnover and sensitivity of human breast carcinoma cells to chemotherapeutic drugs - Dolfi, Sonia C. (2014)
The human homologue of mouse double minute 2 (MDM2) is overexpressed in tumors and contributes to tumorigenesis through inhibition of p53 activity. We investigated the effect of the anti-estrogen fulvestrant on MDM2 expression and sensitivity of estrogen receptor positive human breast cancer cell lines to chemotherapeutics. Fulvestrant down-regulated MDM2 through increased protein turnover. Fulvestrant blocked estrogen-dependent up-regulation of MDM2 and decreased basal expression of MDM2 in the absence of estradiol. As combinations of fulvestrant with doxorubicin, etoposide or paclitaxel were synergistic, altering cell cycle distribution and increasing cell death, this provides rationale for testing combinatorial chemotherapy with fulvestrant as a novel therapeutic strategy for patients with advanced breast cancer.